Organising Rhetorical Components in Verbal Presentation of Scientific Research Outcomes: A Systematic Scoping Review - Marina Ivanova; Nataliya Mekeko; Nadezhda Arupova (National Research University Higher School of Economics, 2023)
Background: The rhetorical structure of various genres of written scientific communication has been extensively covered in articles by contemporary researchers from different countries. However, the rhetorical structure of oral scientific presentations accompanying the presentation and defence of graduation theses, scientific research, and others has not received the same level of detailed study and attention. Nevertheless, the effectiveness of presenting conducted research significantly influences the degree and depth of its further acceptance by the readership. Purpose: to summarise the literature on the rhetorical structure of verbal presentation of scientific research results accompanied by a presentation.   Materials and Methods: We conducted a search of the Scopus bibliographic databases on March 2nd, 2023, and carried out a related grey literature search on March 27th, 2023. We screened the titles and abstracts of the retrieved records. From these records, we extracted demographic characteristics related to the rhetorical structure of oral presentations representing scientific research results. Following this, we extracted passages from empirical studies that described empirically derived moves and steps in speeches during oral presentations. These moves and steps were summarised and presented in the form of a universal matrix for the oral presentation of scientific research results. Results: In the result of the search request 63 articles were found. Having screened all the papers we revealed that only 11 of them met our predetermined inclusion criteria. All these papers were journal research articles. It is worth stating that the majority of the studies were dedicated to rhetorical structure in written presentation of scientific research outcomes and there is a lack of papers related to moves and steps of verbal presentation of scientific research outcomes. Conclusion: This systematic scoping review identified the moves and steps highlighted by authors in the reviewed articles within the oral speech accompanying the presentation of scientific research results to an audience. This matrix can be used to construct a more effective oral presentation of scientific research outcomes. Limitations of the work include the restriction to English language articles and the fact that the methodological quality of the articles included in our extraction was not assessed.